Eva lua tion of the effect of preoperative Lorazepam on post. operative vomiting - Fereshteh Salmani (Iran University of Medical Sciences, 1998)
Lorazepam is widely used preoperatively for anxiolysis/sedation. Lorazepam has been reported to decrease the incidence of chemotherapy induce vomiting. However, the effect of lorazepam on postoperative vomiting has not been studied. The purpose of this study was to evaluate the effect of preoperative lorazepam on postoperative vomiting. This study is a semi-experimental survey about the antiemetic effect of lorazepam as a premedication after cataract surgery in one of the hospitals of Iran Medical Sciences University in 1994. Samples were 80 ASAI,II (7-81) year old patients who went under to cataract extraction under general anesthesia. 40 samples were randomized to receive 25 ~g/kg Lorazepam orally as premedication within 30 min. prior to anesthetic induction. A control group was included. Anesthesia consisted of thiopentan, fentanyl, halothane, nitrousoxide in oxygen and succinylcholine. Patients were observed for vomiting in the early phase «2 hr post-op) and late phase (>2 hr post-op) • Results of the study were presented in 20 tables. Statistical test used to calculate the results were "I" test, chi-square, and cochran. The first hypothesis survey of the antiemetic effect of preoperative lorazepam orally on postoperative vomiting of early phase after cataract surgery with G.A is not supported by results. (X2 = 2.58).But the second hypothesis, (the antiemetic effect of preoperative lorazepam orally on postoperative vomiting of late phase after cataract surgery with G.A) is supported (X2 = 9.02). Lorazepam as premedication resulted in a significantly lower incidence of postoperative vomiting in late phase (p<O.OOl). Based on the findings of the research recommendations for further research are presented and application of results in nursing service are made.